PENDIDIKAN KARAKTER MELALUI KISAH TOKOH SEJARAH LOKAL DALAM KURIKULUM MERDEKA - Karima, Elfa Michellia; Firza, Firza; Abianza, Erza (Jazirah: Jurnal Peradaban dan Kebudayaan, 2023)
Education is the embodiment of a nation, a nation that has a strong character is able to make itself a dignified nation. So that the application of character education in the history of education is very good if implemented properly. Character education is also a planned and conscious effort in order to pass on the character one already has while at the same time building even better character, to improve the quality of individuals in society. At present the values of educational character for students are fading. Judging from the fact that today there are many students who have violated the norms of life and many of them are violating the law as is often the case at this time, there are many cases such as brawls, bullying, persecution and sexual violence committed by students at this time. , students who do not respect teachers and parents, students who have a lot of westernized culture, we rarely find nowadays who are proud and use local products. From these problems through history learning can build the character of students. The purpose of this research is to build students' character through past stories of historical figures in the history lesson of the independence curriculum. This study uses a qualitative method that uses technical analysis of literature. The result of this study is to explain the solution to the problem of forming character education through reading and implementing stories of historical figures in the independence curriculum. Learning the formation of the nation's character through stories of the past and a new twist in histiography in Indonesia is the main reason for the need for character education in education; teaching history for the formation of the character of students. Teachers are required to implement it.